A Review on Grammatical Gender Agreement in Speech Production - Wang, Man; Schiller, Niels O. (Frontiers in Psychology, 2019)
Grammatical gender agreement has been well addressed in language comprehension but less so in language production. The present article discusses the arguments derived from the most prominent language production models on the representation and processing of the grammatical gender of nouns in language production and then reviews recent empirical studies that provide some answers to these arguments.